Analysing Grade 9 Technology examination papers’ design and learners’ performance: A case of two schools in KwaZulu-Natal - Mlambo, Philani Brian; Mbatha, Nonjabulo (Research in Social Sciences and Technology- OpenED Network, 2025)
Poor performance in the senior phase Technology has been a challenge for a very long time now, which led to many scholars investigating the issue. This qualitative study was conducted to analyse how Grade 9 Technology teachers design examination papers and how learners perform. To meet the objective of this study, researchers conveniently selected two (2) secondary schools in the Maqongqo area on the outskirts of Pietermaritzburg and collected data through document analysis of Grade 9 Technology examination papers and learners’ scripts. Analysis of the data was done in accordance with Bloom’s taxonomy grid to gauge how cognitive levels were distributed. The theory of Bloom’s taxonomy by Benjamin Bloom (1957) was used to frame this study. The findings emanating from the data show that Grade 9 Technology teachers are unable to align the examination question papers with Bloom's Taxonomy cognitive levels, which leads to learners’ poor performance as the examination papers are poorly structured. In addition, the findings indicated that Grade 9 Technology learners are struggling with the topic of electrical systems and control. Based on the findings, the study recommended that Grade 9 Technology teachers should be subjected to developmental workshops aimed at implementing Bloom’s taxonomy when setting examinations. The department of education should be responsible for the designing of Grade 9 Technology examinations while teachers are getting relevant training.